Perceived Need for Spousal Support in Maternity Care and Psychosocial Challenges among Couples in Abuja, Nigeria (2022)
Globally, implementation of continuous spousal support in maternity care remains a challenge despite being known as one of the best practices during childbirth. This study examined the perceived need for spousal support and psychosocial challenges of maternity care in Abuja, Nigeria. This mixed method survey was carried out among 196 couples who had had at least one child from the selected communities. A structured questionnaire was used to elicit information and was analysed using descriptive statistics. Qualitative data was thematically analysed. The mean age of husbands was 41.12±8.87 years; wives was 35.68±7.94 years. Couples had positive perception of spousal support with husbands (90.9%) and wives (95.7%). The reported presence of spouse at delivery of baby was similar, 34.8% by husbands and 36.9% by wives. Major psychosocial factors identified were work schedule (93.6%) for husbands and marital challenges (95.6%) for wives. Poor communication; couples’ perception of maternity care; distance to facility were their major challenges. The qualitative studies showed some discordant responses in their willingness. The couples had positive perception of spousal support but there is need for increased sensitization of couples as willingness to partake in spousal support is just fair. The hospital environment should be more conducive for spouses.